Modeling The Integration Process of Lean Production Techniques Into Mass Catering Production - Gümüş, Yusuf; Turhan, Kardelen Öykü (International Journal of Contemporary Economics and Administrative Sciences, 2024)
In this study, the integration process of lean production techniques into mass catering production has been investigated, and this integration process has been modeled based on the current conditions of a catering firm using traditional production methods. The main steps of the study consist of literature review, data collection, model formation, and comparative analysis. The model was developed based on data collected from a catering company that has been able to integrate some lean production techniques into its production process and obtained from literature review. In the model, approximately 64 m2 of idle space was identified in the operation, workflow arrangements negatively affecting labor productivitiy were made, and recommendations were provided to reduce high inventory levels. In the comparative analysis stage, the production costs of two businesses were compared by ratioing production volume and labor capacity.